A Dipolar Cycloaddition Reaction To Access 6‑Methyl-4,5,6,7-tetrahydro‑1H‑[1,2,3]triazolo[4,5‑c]pyridines Enables the Discovery Synthesis and Preclinical Profiling of a P2X7 Antagonist Clinical Candidate - Chrovian, Christa C; Soyode-Johnson, Akinola; Peterson, Alexander A; Gelin, Christine F; Deng, Xiaohu; Dvorak, Curt A; Carruthers, Nicholas I; Lord, Brian; Fraser, Ian; Aluisio, Leah; Coe, Kevin J; Scott, Brian; et al. (Journal of medicinal chemistry, 2018)
A single pot dipolar cycloaddition reaction/Cope elimination sequence was developed to access novel 1,4,6,7-tetrahydro-5H-[1,2,3]triazolo[4,5-c]pyridine P2X7 antagonists that contain a synthetically challenging chiral center. The structure–activity relationships of the new compounds are described. Two of these compounds, (S)-(2-fluoro-3-(trifluoromethyl)phenyl)(1-(5-fluoropyrimidin-2-yl)-6-methyl-1,4,6,7-tetrahydro-5H-[1,2,3]triazolo[4,5-c]pyridin-5-yl)methanone (compound 29) and (S)-(3-fluoro-2-(trifluoromethyl)pyridin-4-yl)(1-(5-fluoropyrimidin-2-yl)-6-methyl-1,4,6,7-tetrahydro-5H-[1,2,3]triazolo[4,5-c]pyridin-5-yl)methanone (compound 35), were found to have robust P2X7 receptor occupancy at low doses in rat with ED50 values of 0.06 and 0.07 mg/kg, respectively. Compound 35 had notable solubility compared to 29 and showed good tolerability in preclinical species. Compound 35 was chosen as a clinical candidate for advancement into phase I clinical trials to assess safety and tolerability in healthy human subjects prior to the initiation of proof of concept studies for the treatment of mood disorders.